Cecco Angiolieri : a study - Orwen, Gifford P. (Gifford Phillips), 1910-1997 (U.N.C. Dept. of Romance Languages, 1979)
Volume215 in the North Carolina Studies in the Romance Languages and Literatures series.This volume is a thorough study of Cecco Angiolieri's life and work. Angiolieri was a thirteenth century Italian poet from Siena. Contents include a prefatory note on English translations of Angiolieri's work and general assessments of his work by Italian critics, a chapter placing the poet's life in context of thirteenth and fourteenth century Siena, a chapter treating the dominant topics of his poetry, and a final chapter on style and technique.
Keywords: Angiolieri, Cecco, -- approximately 1258-approximately 1312 -- Criticism and interpretation.; Angiolieri, Cecco, -- approximately 1258-approximately 1312; Angiolieri, Cecco -- 1260-1312; Angiolieri, Cecco.; Italian poetry.; Poésie italienne.; Italian poetry; Middeleeuwen.; poetry.; Poetry; Criticism, interpretation, etc.; Poetry.; Poésie.